Volume 2B: Advanced Manufacturing 2013
DOI: 10.1115/imece2013-65498
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Surface Roughness and Corrosion

Abstract: There are different parameters which can affect electrochemical reactions such as type of electrolyte, velocity, temperature, oxidizing agents, impurities, anode material type and surface treatment. It has been shown that pre-treatment of working electrode (anode) through abrasion techniques is one of the most important parameters affecting on Tafel slopes and consequently corrosion rate. Surface roughness of the metal surface is a major influence on general corrosion, nucleation of metastable pitting and pitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 32 publications
2
34
0
1
Order By: Relevance
“…The results are in good agreement with SEM and potentiodynamic polarization tests. In the case of metals such as aluminum and nickel, the lower corrosion rate was related to the formation of a stable passive film on smoother surfaces as suggested by the authors [3,[12][13][14][15] but in the case of mild steel no stable passive film is formed and rougher surfaces showed less corrosion and lower oxygen content. Generally, more increase in the oxygen content was observed for mild steel indicating more oxides forms on the surface.…”
Section: Eds Analysismentioning
confidence: 86%
“…The results are in good agreement with SEM and potentiodynamic polarization tests. In the case of metals such as aluminum and nickel, the lower corrosion rate was related to the formation of a stable passive film on smoother surfaces as suggested by the authors [3,[12][13][14][15] but in the case of mild steel no stable passive film is formed and rougher surfaces showed less corrosion and lower oxygen content. Generally, more increase in the oxygen content was observed for mild steel indicating more oxides forms on the surface.…”
Section: Eds Analysismentioning
confidence: 86%
“…Rougher surfaces with deeper groves have lower openness (ratio of width to depth at opening of the grooves) which limit the diffusion of the corrosive ions out of the formed grooves, hence have a higher possibility to grow larger. On smooth surfaces however the formation of stable passive film is more possible to occur which will result in less corrosion [15]. In our case, coatings with nickel chloride concentration lower than 0.25M proved to have positive skewness, expected to have superior corrosion resistance than others.…”
Section: Resultsmentioning
confidence: 56%
“…This behavior could be related to the roughness of the surface. Toloei et al [30] reported that high surface roughness usually accelerated the corrosion rate due to the less tendency of surface to create a complete passive layer. Totally, the lowest corrosion rate corresponded to the Ni-P-10M-20S coating.…”
Section: Electrochemical Test Resultsmentioning
confidence: 99%